Araucaria heterophylla resin-coated magnetic nanosorbent: a greener approach for the abatement of Mesotrione and Metsulfuron methyl herbicides. Issue 10 (9th August 2022) - Manzoor, Suryyia; Ansari, Tariq Mahmood; Arslan, Muhammad; Intizar, Aansa; Fatima, Aafia; Mujahid, Muhammad; Hanif, Muhammad Asif
ABSTRACT: The present study reports the synthesis of a green sorbent using Araucaria heterophylla resin coated on magnetic nanoparticles for the efficient abatement of herbicides; Mesotrione and Metsulfuron methyl from aqueous solution. Characterisation of the sorbent was done by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) that confirmed coated nanoparticles as small agglomerates containing various functional groups. Optimisation of pH, initial concentration and contact time were performed to achieve maximum adsorption. In addition to this, Freundlich and Langmuir isotherm models have been applied to study the adsorption behaviour of these herbicides. Maximum percentage removal of 92% and 88% for Mesotrioneand metsulfuron methyl was obtained respectively. Adsorption process followed Langmuir isotherm and q max of 18.3 mg/g (Mesotrione) and 9.3 mg/g (metsulfuron) were found. The synthesised nanoparticlesare biocompatible, cost effective and can be regenerated for multiple cycles of adsorption.